Is domestic violence during COVID-19 in lactating women related to infantile colic? An important question - Masoumeh Simbar; Zahra Kiani; Negin Shaterian; Mohammadamin Jandaghian Bidgoli; Negar Shaterian; Ghasem Bayani; Farzaneh Rashidi; Maliheh Nasiri (BMC, 2024)
Abstract Background Psychosocial factors such as maternal stress in lactating women were shown to be related to an increased risk of infantile colic because the infants can be affected through breast milk. Therefore, domestic violence against lactating mothers can be effective on the infants' health. It is also demonstrated that domestic violence against women has increased following the COVID-19 pandemic and quarantine. Therefore, this study aims to assess the relationship between domestic violence against breastfeeding women during COVID-19 and the incidence of infantile colic. Methods This was a case-control study that was conducted on 356 lactating mothers who attended Bentolhoda Hospital in Bojnoord-Iran from November 2021 to August 2022. The participants were exclusively breastfeeding mothers who were under 6 months infants. Mothers with and without infantile colic infants were considered the case and control groups, respectively. Two questionnaires were used for data collection including a demographic questionnaire, and a questionnaire to assess domestic violence against women during the quarantine period of Corona pandemic. The data was analyzed using SPSS-V22 and Pearson Spearman correlation and linear regression tests. Results The results showed that women in the case group had a significantly higher score for "sexual violence and restraint" than women in the control group [0.59 ± 0.34 versus 0.62 ± 0.25 (Mean ± SD), respectively] (P < 0.05). The chance of infantile colic was higher among the infants of mothers who experienced domestic violence, but it was not statistically significant (OR = 1.236, P = 0.573). Significant relationships were found between the infantile colic and the history of abortion (OR = 1.430, P = 0.028) and cesarean section (OR = 1.723, P = 0.044). Conclusion Domestic violence during pregnancy can potentially increase infant colic through breast milk. Although our findings need more investigation, it can be recommended to plan the direction of screening for domestic violence and providing the necessary care and counseling to the parents in perinatal care services to prevent infantile colic and improve the infant's health.